Peningkatan Hasil Belajar Materi Perkalian Dua Buah Bilangan Melalui Strategi Pembelajaran Aritmatika Jari Pada Siswa Kelas II SDN Buncitan Sedati Sidoarjo - Saptowati Handayani, Ngunisari (Universitas PGRI Adi Buana Surabaya, 2020)
This research is motivated by the students tend to be passive in learning. Students understand difficult material multiplication of two numbers mathematics courses. Math is one subject that is not favored children. Focus question in this research is